Eavesdropping against bidirectional physical layer secret key generation in fiber communications - Hu, Wenxiu; Wei, Zhuangkun; Leeson, Mark; Xu, Tianhua (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Physical layer secret key exploits the random but reciprocal channel features between legitimate users to encrypt their data against fiber-tapping. We propose a novel tapping-based eavesdropper scheme, leveraging its tapped signals from legitimate users to reconstruct their common features and the secret key.
Keywords: eavesdropping; two-way secret key generation; physical layer security; fiber communications